COMPARISON OF THE STORYTELLING STRUCTURE OF THE NOVEL WEDDING AGREEMENT BY MIA CHUZ AND THE FILM WEDDING AGREEMENT DIRECTED BY ARCHIE HEKAGERY AND ITS RELEVANCE TO LITERATURE LEARNING IN HIGH SCHOOL - Ana Desi Wulandari, Fitri; Sunanda, Adyana (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2023)
This study aims to describe the comparison of the storytelling structure of Mia Chuz's novel Wedding Agreement and the film Wedding Agreement directed by Archie Hekagery and its relevance to literature learning in high school. This study uses qualitative descriptive method. Data collection techniques are carried out by literature study techniques and documentary techniques. There are two sources of data in this study, namely primary data sources and secondary data sources. Primary data sources are obtained from quotes and dialogues in the novel and film Wedding Agreement, while secondary data sources are obtained from Google website links. The data analysis technique of this research uses comparative-inductive techniques and the excranization process. This technique is used to compare data obtained from literary works. The results of this study prove that in the structure of the storytelling in the novel and film Wedding Agreement is broadly the same and those that are translated into films are only taken from the core parts considering that the film is bound by duration. The results of this study find six plot data from novels, seven plot data from films, five background data from the novel, and nine data from the setting. A number of characters are found are 26 characters in the novel and 19 characters in the film Wedding Agreement.